ANALYSIS OF RISK FACTORS OF POWER TRANSMISSION LINE ACCIDENTS DUE TO CLIMATE CONDITIONS - SHTUTS, ANDRII; ZOZULYAK, IHOR; HRYHORENKO, NAZAR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Climate change is becoming one of the most urgent problems of our time, which has a significant impact on all spheres of life, including the energy sector. Power transmission lines (power lines) are a critically important element of the energy infrastructure, ensuring the transportation of electricity over long distances. The increase in extreme weather events, such as hurricanes, floods, droughts and freezing rains, can lead to breakdowns in transmission lines, causing significant losses to the economy and leading to power outages. The paper considers the issue of the functioning of the overhead transmission line. The requirements for maintenance of power lines are given. For the normal functioning of overhead power lines and the prevention of accidents and failures, it is necessary to carry out inspections of wires and cables, measurements of distances and arrows of sag, overhead inspections of wires and cables. Also, an important element for normal functioning is the measurement of distances on overhead power lines under climatic conditions, namely: determination of the height of bouncing of wires and cables when removing ice, determination of the deflection of wires and cables under the influence of wind, determination of distances between wires and between wires and cables by under "galloping" conditions, as the cases listed above can lead to a short circuit, which negatively affects the operation of the transmission line. The algorithm of operation of the overhead transmission line under operating conditions and the requirements for carrying out emergency and restoration work were also analyzed. The work examines in detail the organizational and technical measures for the elimination and prevention of accidents caused by severe climatic conditions, the following issues are considered: determination of the height of bouncing of wires and cables when removing ice, determination of the amount of deflection of wires and cables under the influence of wind, determination of distances between wires and between wires and cables under the conditions of "galloping".